Effectiveness of Noni Fruit (Morinda Citrifolia L.) in Lowering Hypertension : A Systematic Review - Nadiya Fauziyah; Nur Halimah (International Journal of Biomedical Nursing Review, 2023)
Introduction: Hypertension is characterized by symptoms of an increase in systolic blood pressure > 140 mmHg and/or diastolic blood pressure > 90 mmHg11 and is a major contributor to diseases related to blood vessels such as stroke, heart attack, and kidney failure. Generally, most people use chemical drugs to reduce hypertension. Many studies have been conducted to look for chemical drugs with better effectiveness with minimal side effects through traditional medicine, for example using noni fruit. Purpose: This systematic review aims to analyze the effectiveness of noni fruit in reducing hypertension and the relationship between the content of noni fruit that can potentially reduce hypertension. Methods: The design used in this study is a systematic review (Systematic Review) using the Preferred Reporting Items for Systematic Review and Meta-analyses (PRISMA) method. This method is carried out using reviews, analysis, structured evaluations, classifiers, and categorization of evidence-based that have previously been generated. The articles in this study were obtained from electronic databases published in Google Scholar, Pubmed, and Science Direct, which were published from 2013 to 2023. Results: Of the 7 articles showing that noni fruit can reduce hypertension. Noni fruit contains scopoletin and xeronine which have the potential to reduce hypertension. Scopoletin functions to widen narrowed blood vessels and can also reduce MDA levels in the body by increasing SOD activity in the body. Antioxidants in noni can inhibit oxidative stress so that it can reduce hypertension. The active ingredient noni scopoletin functions to normalize blood pressure with an effect similar to the workings of spasmolytic antihypertensive drugs. Characterized by the dilation of blood vessels (vasodilation) due to smooth muscle relaxation. In addition, the content of proxeronine, which is needed by the body to produce xeronine, is a diuretic by increasing fluid volume by expelling fluids through urine and contains potassium in acids that can reduce cholesterol (LDL) which affects blood vessels so that blood pressure can decrease. Conclusion: Noni fruit can reduce hypertension because it contains antioxidants, scopoletin, and proxeronine.